2018
DOI: 10.24874/jsscm.2018.12.02.08
|View full text |Cite
|
Sign up to set email alerts
|

MHD Natural Convective Heat Generation/Absorbing and Radiating Fluid Past a Vertical Plate Embedded in Porous Medium–an Exact Solution

Abstract: The present work reveals the examination of the characteristics of MHD free convective radiating fluid past a permeable plate with the occurrence of thermal transmission and heat source/sink along with changeable concentration and temperature. An exact solution has been employed by usual Laplace transform technique. The effects of diverse parameters on flow velocity, hotness and concentration are discussed through graphical representations and tables. With the incidence of heat source, the fluid velocity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Amine et al 3 reported on MHD natural convection of a triangular cavity involving Ag-MgO/water hybrid nanofluid and provided with a rotating circular barrier and a quarter circular porous medium at its rightangled corner. Chandra Reddy et al [4][5][6][7] studied and reported MHD nanofluid flow properties past a moving vertical plate in the presence of radiation and thermal diffusion and also MHD natural convective heat generation/absorbing and radiating fluid past a vertical plate embedded in a porous medium. Eid et al [8][9][10] gave detailed experimental characterization, TDDFT-DFT, and spin effect on [PEG/H 2 O-ZrO 2 /TiO 2 ] h hybrid nanofluid 3D flow as potential ceramic industry application and also reported on 3D Prandtl nanofluid flow with higher-order chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Amine et al 3 reported on MHD natural convection of a triangular cavity involving Ag-MgO/water hybrid nanofluid and provided with a rotating circular barrier and a quarter circular porous medium at its rightangled corner. Chandra Reddy et al [4][5][6][7] studied and reported MHD nanofluid flow properties past a moving vertical plate in the presence of radiation and thermal diffusion and also MHD natural convective heat generation/absorbing and radiating fluid past a vertical plate embedded in a porous medium. Eid et al [8][9][10] gave detailed experimental characterization, TDDFT-DFT, and spin effect on [PEG/H 2 O-ZrO 2 /TiO 2 ] h hybrid nanofluid 3D flow as potential ceramic industry application and also reported on 3D Prandtl nanofluid flow with higher-order chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Chamkha et al 4 reported on the analysis of non-Newtonian fluid flow past an inclined plate. Chandra Reddy et al [5][6][7] analyzed the MHD flows under the existence of a variety of physical parameters by using Laplace transform technique as well as a numerical method. Computational fluid dynamics analysis on MHD parabolic as well as elliptic flows is clearly explained by Hughes et al 8 The basics related to Hartmann flow and Couette flow are clearly explained in it.…”
mentioning
confidence: 99%